Implementasi Pendidikan Multikultural di Tarbiyatul Muâ€™allimien Al-Islamiyah (TMI) Putri Al-Amien Prenduan - Dewi Nurhayati; Anisah Zulfa; Moh. Wardi (Tafhim Al-'Ilmi, 2022)
Abstract This study aims to determine the implementation of multicultural education at TMI for Female Al-Amien Prenduan which is describe the multicultural condition, the implementation of multicultural education and the supporting and inhibiting factors from the implementation of multicultural education at TMI for Female Al-Amien Prenduan. By using descriptive qualitative techniques, data collection techniques through field methods, observations, interviews and observations were carried out as an initial meeting to collect data. The results showed that the implementation of multicultural education was already diverse with the presence student with the different backgrounds, ethnicties, regions and languages which combined with official languages, Arabic and English. The implementation can be seen from the replacement of various female students in different hostel interactingÂ  with each other. And the suporting factors was a system that has exited since the beginning, and the inhibiting factor was a student fanaticism. Kata Kunci: Implementasi, Pendidikan, Multikultural.